NGC 6124: a young open cluster with anomalous- and fast-rotating giant stars. Issue 4 (5th October 2021) - Holanda, N; Drake, N A; Corradi, W J B; Ferreira, F A; Maia, F; Magrini, L; da Silva, J R P; Pereira, C B
ABSTRACT: We present the results of a chemical analysis of fast and anomalous rotator giants members of the young open cluster NGC 6124. For this purpose, we carried out abundances of the mixing sensitive species such as Li, C, N, Na, and 12 C/ 13 C isotopic ratio, as well as other chemical species for a sample of four giants among the seven observed ones. This study is based on standard spectral analysis technique using high-resolution spectroscopic data. We also performed an investigation of the rotational velocity (v i ) once this sample exhibits abnormal values – giant stars commonly present rotational velocities of few km s −1 . In parallel, we have performed a membership study, making use of the third data release from ESA Gaia mission. Based on these data, we estimated a distance of d = 630 pc and an age of 178 Myr through isochrone fitting. After that procedure, we matched all the information raised and investigated the evolutionary stages and thermohaline mixing model through of spectroscopic T eff and g and mixing tracers, such as 12 C/ 13 C and Na, of the studied stars. We derived a low mean metallicity of [Fe/H] = −0.13 ± 0.05 and a modest enhancement of the elements created by the s-process, such as Y, Zr, La, Ce, and Nd, which is in agreement with what has already been reported in the literature for young clusters. The giants analysed have homogeneous abundances, except for lithium abundance [ ε (Li)NLTE = 1.08 ± 0.42] and this may be associated with a combination of mechanisms that act increasing or decreasing lithium abundances in stellar atmospheres.